2013
DOI: 10.1007/s10509-013-1491-5
|View full text |Cite
|
Sign up to set email alerts
|

On the holographic dark energy in chameleon scalar-tensor cosmology

Abstract: We study the holographic dark energy (HDE) model in generalized Brans-Dicke scenario with a non-minimal coupling between the scalar field and matter lagrangian namely Chameleon Brans Dicke (CBD) mechanism. In this study we consider the interacting and non-interacting cases for two different cutoffs. The physical quantities of the model such as, equation of state (EoS) parameter, deceleration parameter and the evolution equation of dimensionless parameter of dark energy are obtained. We shall show that this mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…Using definition of n s and this fact that d d ln k = − d dN , combination of Eqs. (40) and (42) yields…”
Section: Chaotic Inflationmentioning
confidence: 98%
“…Using definition of n s and this fact that d d ln k = − d dN , combination of Eqs. (40) and (42) yields…”
Section: Chaotic Inflationmentioning
confidence: 98%
“…There are many studies on this topic such as [184][185][186][187][188][189][190][191][192], where the authors explain that there are two definitions for the Lagrangian of a perfect fluid as L (2) m = p, respectively. However, in our case, this degeneracy is broken due to the non-minimal interaction of the scalar field and matter, and therefore we follow the approach proposed in [192], where it is shown that only for L (2) m = p one has a geodesic motion for perfect fluids.…”
Section: )mentioning
confidence: 99%
“…Also, much attempts have been done to reconstruct scalar field DE models, from HDE and ADE [42][43][44][45][46]. In some of them the coupling between the scalar field and DM Lagrangian, called chameleon, has been considered [47][48][49]. Tachyon scalar field motivated from string theory is a especial scalar field which can explain the whole history of the Universe from inflation to late time acceleration [50][51][52][53][54][55][56][57][58][59].…”
Section: Issn: 2641-886xmentioning
confidence: 99%